مساهمة في تقييم أنماط وممارسات استهلاك المياه المنزلية في محافظة طرطوس - العلي, يوسف; شيخو, طاهر (Latakia University Journal -Biological Sciences Series, 2014)
يزداد النشاط الاقتصادي والضغط الديموغرافي في محافظة طرطوس،في الوقت الذي تعاني فيه بعض قراها من شح مياه الشرب، مما يجعل ترشيد استهلاك المياه مسألة ملحة. تهدف هذه الدراسة إلى التعرف على أنماط وممارسات استهلاكالمياه المنزليةلدى عينة من مشتركي المياه المنزلية في محافظة طرطوسلتحديد الإجراءات التي يمكن من خلالها ترشيد استهلاك مياه الشرب. أجري لهذا الغرض استبيان شمل 150 فرداً من المشتركين بالمياه، حيث وزعت على كلٍ منهم استمارة تضمنت 20 سؤالاً، ثمأخضعت الإجابات لتحليل أحصائي. أشارت النتائج إلى وجود نسبة مرتفعة(95.3 %) من المبحوثين يتبعون إجراءات لترشيد استهلاك المياه، وانخفاض نسبة الذين يملكون تجهيزات تحد من استهلاك المياه (4.7 %). وقد عارض غالبية الذين شملهم الاستبيان (87.3%) اللجوء إلى زيادة سعر الماء كإجراء للحد من استهلاك المياه. خلصت الدراسة إلى وجود وعي مائي جيد لدى الذين شملهم الاستبيان يمكن الارتكاز عليه لترشيد مياه الشرب في المحافظة من خلال حملات التوعية. The problem of drinking water scarcity exacerbates in some villages in Tartous governorate making water conservation a priority. The aim of this study is to identify the patterns and practices of household water consumption of a sample of water subscribers in Tartous governorate in order to determine the procedures through which to rationalize the consumption of drinking water. For this purpose, a survey of 150 household water subscribers was conducted. The answers were then subjected to a statistical analysis. The results indicated the presence of a high percentage of those who follow the procedures for rationalizing the consumption of water within the sample (95.3%), and a low percentage of those who have the techniques for reducing water consumption (4.7%). The majority of those surveyed (87.3%) objected to increasing the price of water as a measure to reducing water consumption. The study revealed that there is a good aqueous awareness in the governorate on which one can rely in rationalizing the consumption of drinking water through awareness campaigns.